Degree of hypertension and subclinical coronary atherosclerosis in asymptomatic individuals without cardiovascular disease - Mi-Hee Jang; Sangwoo Park; Soe Hee Ann; Yong-Giun Kim; Young-Jee Jeon; Soyeoun Lim; Woon-Jung Kwon; Seong Hoon Choi; Hyun Woo Park; Gyung-Min Park (PLoS ONE, 2026)
Objective This study sought to evaluate the association between degree of hypertension and subclinical coronary atherosclerosis. Design and method We analyzed 7,332 asymptomatic individuals (mean age 52.8 ± 7.8 years; 4,680 [63.8%] men) without cardiovascular disease who voluntarily underwent coronary computed tomography angiography (CCTA) as part of a general health examination. Hypertension classification was adapted from the American College of Cardiology/American Heart Association 2025 guidelines. The degree of coronary artery disease (CAD) was evaluated using CCTA and classified as normal coronary arteries, non-obstructive CAD (diameter stenosis <50%), and obstructive CAD (diameter stenosis ≥50%). Results The participants were classified into 4 groups: normal (systolic blood pressure [SBP] <120 mmHg and diastolic blood pressure [DBP] <80 mmHg; n = 2,500), elevated (SBP 120–129 mmHg and DBP < 80 mmHg; n = 969), stage 1 hypertension (SBP 130–139 mmHg or DBP 80–89 mmHg; n = 2,841), and stage 2 hypertension (SBP ≥ 140 mmHg or DBP ≥ 90 mmHg; n = 1,022). After adjusting for cardiovascular risk factors, the stage 1 hypertension group was significantly associated with non-obstructive CAD (adjusted odds ratio [aOR] 1.335; 95% confidence interval [CI], 1.156–1.541). Furthermore, the stage 2 hypertension group had a significant association with both non-obstructive CAD (aOR, 1.483; 95% CI, 1.234–1.784) and obstructive CAD (aOR, 1.696; 95% CI, 1.194–2.409). Conclusions In this large cross-sectional study, the degree of hypertension was associated with an increased risk and severity of subclinical coronary atherosclerosis. These findings highlight the potential importance of early recognition of blood pressure elevation and cardiovascular risk stratification in asymptomatic individuals.